Does a classroom standing desk intervention modify standing and sitting behaviour and musculoskeletal symptoms during school time and physical activity during waking time? - Ee, Jolyn; Parry, Sharon; de Oliveira, Beatriz; McVeigh, Joanne; Howie, Erin; Straker, Leon (Molecular Diversity Preservation International (MDPI), 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Children are increasingly spending more time sedentary at school and during leisure time. This study examined the effects of a standing desk intervention in a classroom on children’s standing and sitting time at school, sedentary and physical activity levels throughout the day (waking hours), and musculoskeletal discomfort. A within-subjects crossover study design was used. Participants used either a standing desk or traditional seated desk for 21 days before swapping desks for another 21 days. Accelerometry and musculoskeletal discomfort data were collected during the last seven days of each 21-day period. Mixed models were used to analyse accelerometry data. Zero-inflated regression models and logistic regression models were used to analyse discomfort data. Forty-seven male students (aged 10–11 years) participated in the study. Standing time was 21 min/school day higher (p < 0.001) and sitting time was 24 min/school day lower (p = 0.003) when standing desks were used. No significant differences were found in sedentary and physical activity time during waking hours between the standing desk and seated desk conditions. Students were less likely to report musculoskeletal discomfort in the neck, shoulder, elbows and lower back when using standing desks (OR 0.52–0.74). Standing desks significantly increased classroom standing time and decreased musculoskeletal discomfort reports but had no overall effect on daily physical activity levels. Schools should consider moving towards classrooms enabling a variety of postures to potentially improve the long-term health of children.